INHERITED SHAME AND IDENTITY FRAGMENTATION IN KENZABURŌ ŌE’S THE SILENT CRY: A FREUDIAN PSYCHOANALYTIC APPROACH - Zainasti, Zaimilatun Nuri; Pawiro, Muhammad Ali; Ezir, Ely (JOURNAL OF LANGUAGE, 2025)
This article examines the psychological disintegration of Takashi, the central character in Kenzaburō Ōe’s The Silent Cry, through the lens of Freudian psychoanalysis. Drawing on Sigmund Freud’s structural theory of the psyche—particularly the dynamics of the id, ego, and superego—this study explores how identity crisis, generational trauma, and defense mechanisms shape Takashi’s internal conflict and destructive behavior. The analysis reveals that Takashi’s revolutionary actions are not driven by coherent political ideology, but by inherited shame, repressed grief, and the failure of ego mediation. His descent into violence and mania is interpreted as a symbolic enactment of psychological collapse, wherein inherited guilt and unresolved trauma override rationality and self-regulation. The superego, as portrayed in the novel, functions not only as a moral compass but as a punitive legacy passed through family and cultural memory. This study also highlights the interplay of defense mechanisms—such as projection, rationalization, denial, and sublimation—that ultimately fail to contain his psychic distress. By interpreting The Silent Cry as a narrative of personal and national trauma, this paper demonstrates how literature can serve as a site for exploring deep psychological wounds, especially those stemming from unspoken histories and familial burden.